Pengaruh Big Five Personality terhadap Kecurangan Akademik - Alfarisi, Imam; Sari, Vita Fitria (Universitas Negeri Padang, 2026)
The purpose of this study is to identify and examine how the Big Five personality characteristics affect academic settings. This study falls under the category of quantitative associative causation research. A questionnaire that was given to accounting students at Padang State University, Bung Hatta University, and Andalas University was used by researchers to gather data. Primary data was used in this study. In this instance, test the hypothesis. IBM SPSS's multiple linear regression analysis is used in the study. The study's findings demonstrate that extraversion has a favorable and noteworthy impact on academic circumstances. Academic conditions are not much impacted by personality agreement. Academic situations are significantly impacted by conscientiousness. Academic situations are significantly impacted by personality neuroticism. The openness to experience personality does not have a significant effect on academic conditions